Residential waste in Palmy exposed! - Farrelly, TA; Chrystall, P (WasteMINZ)
The Palmerston North City Council and two social scientists from Massey University have been collaborating in a research project aimed at better understanding Palmerston North residents’ relationships with household waste and recycling since March this year. A key component of the year-long study is a nine-month trial of green, food, and hazardous curb side collections. The recycling and general waste collected from four residential addresses has been audited fortnightly. Three educational workshops were held with the participants to demystify the recycling process and council’s expectations of residents’ recycling and waste practices. A web blog was also created to provide additional resources and advice. Observations from the trial and quantitative data generated by the audits were contextualised in fortnightly interviews with the participating households throughout the year as well as participants’ blog comments and journal entries. The combination of the quantitative and qualitative data collected in this study provided provides a depth of understanding about the impact the trial and the educational support has on the decontamination of recycling collections.